2021
DOI: 10.3389/fendo.2021.649255
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Insulin Gene: Changes in Gene Number, Sequence, and Processing

Abstract: Insulin has not only made major contributions to the field of clinical medicine but has also played central roles in the advancement of fundamental molecular biology, including evolution. Insulin is essential for the health of vertebrate species, yet its function has been modified in species-specific manners. With the advent of genome sequencing, large numbers of insulin coding sequences have been identified in genomes of diverse vertebrates and have revealed unexpected changes in the numbers of genes within g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Directs formation of β and δ cells. Acts as a transcriptional repressor, being especially effective for ghrelin expression and pax6-mediated glucagon expression [120][121][122][123][124] ins (insulin) Provides instructions for producing the insulin hormone [125] mafa (v-maf musculoaponeurotic fibrosarcoma oncogene family, protein A)…”
Section: Pax4 (Paired Box Gene 4)mentioning
confidence: 99%
“…Directs formation of β and δ cells. Acts as a transcriptional repressor, being especially effective for ghrelin expression and pax6-mediated glucagon expression [120][121][122][123][124] ins (insulin) Provides instructions for producing the insulin hormone [125] mafa (v-maf musculoaponeurotic fibrosarcoma oncogene family, protein A)…”
Section: Pax4 (Paired Box Gene 4)mentioning
confidence: 99%
“…The AgosIRP10 homologous genes are conserved among four aphid species, with almost identical amino acid sequences at the C‐terminal. In contrast, the AgosIRP4 and AgosIRP5 homologous genes are conserved across aphid species at the N‐terminal, suggesting that these genes may have evolved, diverged, and duplicated from a common ancestor (Figure 2 ; Irwin, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the majority of vertebrates, rats are exclusively equipped with two independent insulin-encoding genes, Ins1 and Ins2 . The evolutionary explanation is based on the complementary functions of two insulin-encoding regions that have enabled adaptation to different environments [ 42 ]. In other words, without the simultaneous expression of rat Ins1 and Ins2 genes, insulin could not be synthesized in rats, in contrast to humans, in which a single human INS encodes insulin.…”
Section: Melatonin Signaling Pathways In T2dmmentioning
confidence: 99%
“…In other words, without the simultaneous expression of rat Ins1 and Ins2 genes, insulin could not be synthesized in rats, in contrast to humans, in which a single human INS encodes insulin. Despite a lack of evidence confirming the tight association between INS and Ins1 , reports have suggested that the INS and Ins2 structures are very similar, with three exons separated by two introns [ 42 ]. To confirm the similar function of INS and Ins2 , Karaca et al [ 43 ] were the first to integrate the human INS gene into Ins1/Ins2 double-knockout rats, and they found low insulin production in the transgenic groups.…”
Section: Melatonin Signaling Pathways In T2dmmentioning
confidence: 99%